THE EFFECTIVENESS OF OCCUPATIONAL SAFETY AND HEALTH (OSH) IMPLEMENTATION IN MELALEUCA FOREST HARVESTING, INDONESIA. - Septiana, Ratih Madya (Tengkawang : Jurnal Ilmu Kehutanan, 2025)
Melaleuca cajuputi is a pioneer tree species known as the ‘swamp-tea tree’ and a versatile forest plant whose leaves and twigs can be processed into melaleuca oil containing cineol. It is recognized as a secondary traditional medicinal ingredient. Melaleuca leaf harvesting is a crucial part of the technical production of melaleuca oil forest products. Harvesting occurs across various topographies, utilizing dangerous tools and equipment. Therefore, it is essential to evaluate the effectiveness of implementing OSHMS and its impact on work-related accidents and workers' health during melaleuca leaf harvesting activities. The study aims to identify the current situation of workers, clarify the technical aspects of leaf harvesting, and evaluate the effectiveness of implementing The occupational Safety and Health Management System (OSHMS) and hazard risk identification. The research was conducted in a forest area managed by the provincial government on Java Island, chosen because it has the largest population of melaleuca trees. The study’s methods included interviews, literature review, and field observation related to the implementation of OSHMS, the current state of employees, harvesting activities, hazard levels, and incidents that occurred during these activities. The results show that the average worker age is 58 years, and all are male. About 64% have at least an elementary school education. The average land ownership for workers involved in melaleuca leaf harvesting is 0.17 hectares. The implementation of OSHMS in leaf harvesting is inadequate due to the provincial government's lack of a proper procedure. Eighty percent of workers experience health issues related to their job activities. The highest risks of accidents involve being hit by an axe or machete. Keywords: forest worker, Melaleuca cajuputi, OSHMS. Abstrak Kayu putih adalah spesies pohon pionir yang dikenal sebagai ‘pohon teh rawa’ dan tanaman hutan serbaguna yang daun dan rantingnya dapat diolah menjadi minyak yang mengandung cineol. Tanaman ini diakui sebagai bahan obat tradisional sekunder. Pemanenan daun kayu putih merupakan bagian penting dari proses produksi minyak kayu putih. Pemanenan ini dilakukan di berbagai topografi, dan menggunakan peralatan tajam serta berbahaya. Oleh karena itu, penting untuk menganalisis efektivitas penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) serta dampaknya terhadap kecelakaan kerja dan kesehatan pekerja selama aktivitas pemanenan. Studi ini bertujuan untuk mengidentifikasi kondisi pekerja, menjelaskan rangkaian kegiatan teknis pemanenan kayu putih, dan mengevaluasi efektivitas penerapan SMK3 serta mengidentifikasi risiko bahaya yang terjadi. Penelitian dilakukan di kawasan hutan yang dikelola oleh pemerintah provinsi di Pulau Jawa, pemilihan Lokasi dengan alasan karena memiliki populasi tegakan kayu putih terbesar. Metode penelitian ini meliputi wawancara, tinjauan literatur, dan pengamatan lapangan terkait dengan implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3), kondisi karyawan saat ini, aktivitas pemanenan, tingkat bahaya, dan kecelakaan yang terjadi selama pemanenan daun kayu putih. Hasil menunjukan bahwa usia rata-rata pekerja adalah 58 tahun, dan semuanya laki-laki. Sekitar 64% memiliki pendidikan minimal sekolah dasar. Rata-rata kepemilikan lahan bagi pekerja yang terlibat dalam pemanenan daun kayu putih adalah 0,17 hektar. Penerapan SMK3 dalam pemanenan daun kayu putih masih kurang memadai karena pemerintah provinsi belum memiliki prosedur yang standard. Delapan puluh persen pekerja mengalami masalah kesehatan akibat aktivitas ini. Risiko kecelakaan tertinggi adalah terkena tebasan kapak atau parang. Kata kunci: Kayu putih, Pekerja Hutan, SMK3.